(3cJGH BOGH CHj GdYHGS YHO Gddg Hf GdeYJRs - (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s ((3Ydi Hf CMeO Hf eMeO GdcGJH s)
(3ChdgG (B:s
(3bGd CHh GdYHGS YHO Gddg Hf GdeYJR QMeg Gddg GdCOH UhQI GdYbd aMSf Ybdc cja THHJ GdehJ HGH GdCNQI s
(3BNQgG (B:s
(3GQMe Pd GdCbQGQ ef SWhI GdYbGH CfeG jfWb GdYGde HGdYGQa fLR HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B154 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B443s
Keywords: (3GdadSaI hGdefWbs